EFFECT OF TOLO BEAN FLOUR (Vigna unguiculata) SUBSTITUTION ON ORGANOLEPTIC TESTS AND PROTEIN CONTENT IN STEAMED BOLU - Nurul Hidayati (International Journal of Social Science, 2021)
Indonesia is an agricultural country that has a unique diversity of agricultural products. Where each region has different agricultural products according to their environment. Tolo beans are local food ingredients that are easily found in Indonesia. The yield potential of tolo beans is quite high, reaching tons/hectare to 2 tons/hectare and is determined by the variety. This study aims to determine the substitution of tolo beans on steamed cakes with different additions, protein content and organoleptic tests. Experimental design research, using a completely randomized design (CRD) with the addition of tolo beans (50gr, 75gr, 100gr). Untrained panelists were 25 adults around the researcher's house in Madura and analyzed for protein levels. The results of the protein content of 14.05 grams using the Kjeldahl method. The results of the research on the substitution of tolo beans showed that there was an effect on the results of organoleptic tests of color, aroma, texture, taste and preference. Laboratory test for steamed sponge cake with tolo bean substitution. The result of the highest protein content in BK3 is 14.05mg/100g and the lowest protein content in BK1 was 6.81 mg/100g